2021
DOI: 10.1126/science.aba1786
|View full text |Cite
|
Sign up to set email alerts
|

Transient rest restores functionality in exhausted CAR-T cells through epigenetic remodeling

Abstract: T cell exhaustion limits immune responses against cancer and is a major cause of resistance to chimeric antigen receptor (CAR)–T cell therapeutics. Using murine xenograft models and an in vitro model wherein tonic CAR signaling induces hallmark features of exhaustion, we tested the effect of transient cessation of receptor signaling, or rest, on the development and maintenance of exhaustion. Induction of rest through enforced down-regulation of the CAR protein using a drug-regulatable system or treatment with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
269
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 374 publications
(318 citation statements)
references
References 83 publications
(124 reference statements)
13
269
3
Order By: Relevance
“…In this way SIRT1 acts as an epigenetic promoter of immune exhaustion ( 18 , 194 ). In a follow-up CAR T study, the incorporation of a titratable FK506 binding protein 12 (FKBP) destabilizing domain (DD) emphasized the importance of timing and rest ( 195 ). Simply put, this engineered CAR T cell model demonstrated that interrupting tonic T cell activation, either through the titratable FK506 DD or through dasatinib, a tyrosine kinase inhibitor, could block epigenetic-mediated immune exhaustion.…”
Section: Bioengineering Approaches To Reverse Epigenetic-mediated Immune Exhaustion and Suppressionmentioning
confidence: 99%
“…In this way SIRT1 acts as an epigenetic promoter of immune exhaustion ( 18 , 194 ). In a follow-up CAR T study, the incorporation of a titratable FK506 binding protein 12 (FKBP) destabilizing domain (DD) emphasized the importance of timing and rest ( 195 ). Simply put, this engineered CAR T cell model demonstrated that interrupting tonic T cell activation, either through the titratable FK506 DD or through dasatinib, a tyrosine kinase inhibitor, could block epigenetic-mediated immune exhaustion.…”
Section: Bioengineering Approaches To Reverse Epigenetic-mediated Immune Exhaustion and Suppressionmentioning
confidence: 99%
“…Here, we focus on the development of more specific and potent next-generation engineered T cell therapies for mesothelioma and ovarian cancer. Mesothelioma is a highly aggressive chronic inflammationdriven cancer with an exceedingly poor prognosis that has three histological subtypes: epithelioid (69% of cases, median overall survival ~14 months), biphasic (12%, ~10 months), and sarcomatoid (19%, ~4 months) (7,8). Mesothelioma is inherently hard to treat with traditional modes of cancer therapy, and recent trials exploring mono-or combination immune checkpoint inhibitors (ICIs) have also had limited impact (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has demonstrated that transient rest in CAR expression potentiates T cell function by reversing premature exhaustion driven by CAR signaling in the absence of tumor antigen. 7 Consistent with this notion, both manuscripts argue that synNotchgated CAR expression maintains T cells in a less differentiated and exhausted state, resulting in enhanced anti-tumor immunity. However, it is worth noting that while constitutively expressed bispecific IL-13Ra2/EphA2 CAR-T and EGFRvIII CAR-T cells exhibit comparably high exhaustion marker expression, EGFRvIII CAR-T cells retain functionality in vivo whereas bispecific IL-13Ra2/EphA2 CAR-T cells are completely ineffective.…”
mentioning
confidence: 75%